Adhesion strength and anti-tumor agents regulate vinculin of breast cancer cells - Metsiou, Despoina Nektaria; Deligianni, Despina; Giannopoulou, Efstathia; Kalofonos, Haralabos; Koutras, Angelos; Athanassiou, George (Frontiers in Oncology, 2022)
The onset and progression of cancer are strongly associated with the dissipation of adhesion forces between cancer cells, thus facilitating their incessant attachment and detachment from the extracellular matrix (ECM) to move toward metastasis. During this process, cancer cells undergo mechanical stresses and respond to these stresses with membrane deformation while inducing protrusions to invade the surrounding tissues. Cellular response to mechanical forces is inherently related to the reorganization of the cytoskeleton, the dissipation of cell–cell junctions, and the adhesion to the surrounding ECM. Moreover, the role of focal adhesion proteins, and particularly the role of vinculin in cell attachment and detachment during migration, is critical, indicating the tight cell–ECM junctions, which favor or inhibit the metastatic cascade. The biomechanical analysis of these sequences of events may elucidate the tumor progression and the potential of cancer cells for migration and metastasis. In this work, we focused on the evaluation of the spreading rate and the estimation of the adhesion strength between breast cancer cells and ECM prior to and post-treatment with anti-tumor agents. Specifically, different tamoxifen concentrations were used for ER+ breast cancer cells, while even concentrations of trastuzumab and pertuzumab were used for HER2+ cells. Analysis of cell stiffness indicated an increased elastic Young’s modulus post-treatment in both MCF-7 and SKBR-3 cells. The results showed that the post-treatment spreading rate was significantly decreased in both types of breast cancer, suggesting a lower metastatic potential. Additionally, treated cells required greater adhesion forces to detach from the ECM, thus preventing detachment events of cancer cells from the ECM, and therefore, the probability of cell motility, migration, and metastasis was confined. Furthermore, post-detachment and post-treatment vinculin levels were increased, indicating tighter cell–ECM junctions, hence limiting the probability of cell detachment and, therefore, cell motility and migration.